Diversity of Land Insect in Polda Plantation South Sulawesi - Muh Yunus; Muh Sri Yusal; Andi Nur Samsi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Land insects function in the soil fertility process, assist the soil decomposition, and to accelerate soil material cycle so as there are equilibrum on food chains  and food webs cycle. The study aimed to examine of land insects in the South Sulawesi Regional Polda plantation and their surrounding environment benefits. The sampling technique was purposive sampling with an exploratory method, namely direct observation or observation in the field using the Pitffal Trap method at 5 stations. The study results at the South Sulawesi Regional Polda plantation obtained 172 individuals of soil insects consisting of 14 genera in 13 families. The land insects of Carabidae and Gryllidae families are insect genus with high abundance, while the families of Pentatomidae, Alydidae, Syrphidae, Saturniidae, Stratiomyidae, Blattidae, and Gryllotalpidae families has low abundances. The causing land insects genera high abundance at several research stations are the presence of supportive environmental conditions, where the habitats of some of these land insects are still preserved or natural, abundant food sources, and locations far from residential areas. The land insects found act as pollinators, decomposers, predators, parasitoids and bioindicators.